2022
DOI: 10.1111/1759-7714.14479
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of induced oligometastasis and repeated oligoprogression of advanced lung adenocarcinoma with immunotherapy and radiotherapy

Abstract: Highly active and durable systemic therapies such as targeted therapy and immunotherapy can convert widespread metastatic disease into oligometastatic status, for which metastasis-directed local intervention can control and potentially prolong survival. Radiation therapy is an effective therapeutic option for oligometastatic and oligoprogressive disease. Here, we present a case of induced oligometastasis and repeated oligoprogressive lung cancer in which more than 6 years of survival was achieved with a combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Unfortunately, while DLTs, particularly SRT, are widely used in clinical practice to manage OMD, there is limited evidence to support their use. A review of scientific literature from PubMed in the past year (when a peak of publications is registered) reveals a high number of heterogeneous, retrospective, and small-scale clinical studies conducted in real-world settings [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. While these studies are important, their results cannot formally change the standard of therapy.…”
Section: Definitive Local Therapies In Omdmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, while DLTs, particularly SRT, are widely used in clinical practice to manage OMD, there is limited evidence to support their use. A review of scientific literature from PubMed in the past year (when a peak of publications is registered) reveals a high number of heterogeneous, retrospective, and small-scale clinical studies conducted in real-world settings [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. While these studies are important, their results cannot formally change the standard of therapy.…”
Section: Definitive Local Therapies In Omdmentioning
confidence: 99%
“…While these studies are important, their results cannot formally change the standard of therapy. The evidence ranges from case reports and retrospective series [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ] to phase III randomized trials [ 69 ] such as the SINDAS trial. This trial showed that adding SRT to TKIs significantly improves survival in 133 EGFR-mutated NSCLC OMD patients (median OS TKI plus SRT: 25.5 months vs. 17.4 months in TKI monotherapy).…”
Section: Definitive Local Therapies In Omdmentioning
confidence: 99%